(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the prospects of maintaining a sustained remission by prolonged initial phase steroid therapy in nephrotic syndrome. Design: Hospital based descriptive study. Place and Duration: Department of Pediatric Medicine, Combined Military Hospital, Lahore, Pakistan. January 2002 to January 2010. Patients and Methods: Fifty children of both genders in their very first episode of steroid sensitive nephrotic syndrome (SSNS) were selected after an informed parental consent. Prednisolone was used in a gradually tapering dose spread over 7 months with a post-treatment 12-month follow up. Albuminuria was monitored by dipstick method. Results: Thirty five (70%) boys and 15 (30%) girls participated in the study with male to female ratio of 2.3:1. Mean age was 4.62±2.15 years. All the patients became albuminuria-free within first 4 weeks of treatment. Thirty two (64%) patients maintained remission during the study and 12-month follow-up period. Eighteen (36%) case relapsed within 6 months after completion of initial treatment. Eight (16%) of these 18 cases had multiple relapses. Cushingoid appearance and mild hypertrichosis was noted in all the 50 (100%) cases. Conclusion: Prolonged initial phase tapering steroid therapy helps maintain a sustained and longer remission in SSNS. It should be adopted as the standard regimen.